PENGARUH PROFITABILITAS, OPINI AUDIT, UKURAN DAN UMUR PERUSAHAAN TERHADAP AUDIT DELAY PADA PERUSAHAAN FOOD AND BEVERAGES TAHUN 2015-2019 - Dinda Adelia Pradhitasari; Pardi Pardi (ITB AAS INDONESIA, 2021)
This research was conducted at Food and Beverages companies listed on the Indonesia Stock Exchange in 2015-2019. The objective of this research is to determine the effect of company size, profitability, audit opinion and company age on audit delay. The research method uses quantitative research methods. The population is all Food and Beverages companies listed on the Indonesia Stock Exchange with a sample of the Food and Beverages research in 2015-2018, namely 14 companies using purposive sampling. The analysis tool used is Multiple Linear Regression Analysis. The results of data analysis can be concluded that there is a company size that has an effect on audit delay in food and beverages companies listed on the IDX 2015-2019. Company profitability has no effect on audit delay in food and beverages companies listed on the IDX 2015-2019. Auditor's opinion has no effect on Audit delay in food and beverages companies listed on the IDX 2015-2019. Company age has an effect on audit delay in food and beverages companies listed on the IDX 2015-2019. Keywords : Profitability, Audit Opinion, Audit delay